KANDUNGAN SENYAWA AKTIF MAKROALGA YANG DIAMBIL DI PERAIRAN PANTAI ARUBARA KABUPATEN ENDE - Arlinda Malo; Yuliana Saloso; Sunadji Sunadji (Nusa Cendana University, 2018)
Abstract - This study aims to determine the content of active compounds of macroalgae the taken in Arubara coastal waters of Ende regency. The method used in this research is descriptive analysis by table and diagram. The results showed each macroalgae sample contains active compounds such as flavonoids, phenolics, tannins and saponins and no contains alkaloids. Keywords : Active Compound, Macroalgae